INOVASI METODE PEMBELAJARAN TAHFIDZ AL-QUR'AN DI MADRASAH TSANAWIYAH NURUL HIDAYAH SIMATORKIS - Nur Hakimah; Alfina Sovia; Dahliati Simanjuntak (Yayasan Baitul Hikmah al-Zain, 2025)
Memorizing the Qur'an is a task that tends to be more difficult than reading and understanding. This happens because in addition to having a very large number of pages, the Qur'an also has nuances of language that are relatively difficult to understand. Memorizing the Qur'an requires a long process, perseverance and resilience are very necessary hard work, a strong memory as well as a great interest and motivation, in order to be able to complete and fluently read 30 juz of the Qur'an. In memorizing the Qur'an, a method is needed so that the memorization process becomes programmed. This method is also expected to help memorization become effective. Madrasah Tsanawiyah Nurul Hidayah Simatorkis is one of the formal educational institutions that places high attention on the Tahfidzul Qur'an program. This study aims to determine the methods used in learning tahfidz Qur'an at Madrasah Tsanawiyah Nurul Hidayah Simatorkis. The research method used is a field review by collecting data directly at the research location. The results of the study show that the method used in learning tahfidz at MTS Nurul Hidayah Simatorkis is the Talaqqi method.